Blood Leukocyte Indices in Young and Aged Rats Under Desynchronosis Initiation Against the Background of Preventive Whole-body Cryostimulation - Lomako, Viktoria; Shylo, Oleksandr (Problems of Cryobiology and Cryomedicine, 2023)
It was speculated that the whole-body cryostimulation (WBC) would adjust the negative effect of desynchronosis on the body. One-time WBC was performed in a cryochamber at –120°C a day before the desynchronosis simulation, which was initiated by shifting the light regimen. The WBC effi cacy was determined by leukocyte parameters of the blood of 6- and 18-monthold rats. Types of leukocytes were counted in blood smears. Integral leukocyte indices were used to assess the immune system state. Preventive application of WBC restored the number of lymphocytes and eosinophils and increased the number of monocytes in rats of both age groups, as well as the total leukocytes count in young animals. In animals of both age groups, young forms of neutrophils predominated, immunoreactivity decreased, the effector link of immunity and the macrophage system were activated. Delayed-type hypersensitivity processes in young rats as well as immediate-type hypersensitivity processes in aged rats were activated, and the reactive response of neutrophils decreased/increased according to the age of the animals. Probl Cryobiol Cryomed 2024; 34(3):201–212